Central Asian Saks (Historical And Ethnographic Information) - U. Abdullaev (Global Scientific Publishing, 2023)
The Article was devoted to the study historically ethnographically of antiquity about Central Asian Peoples of one of the ancestors (Saks). The author firstly provided information in this article on the reflection of the Saks in historical sources. In particular, the analysis of information and opinions about the Saks in the "Avesto", ancient Greek and Chinese sources One of the main aspects of the article is that it contains interesting information about the social life and customs of the Saks. The author has analyzed many sources and literature on the subject.
Keywords: main; information; interesting; Avesto